Assessment of Right Ventricular Function, Blood Lactate Levels, and Serum Peptidomics Profiles Associated With Mitral Valve Disease in Dogs - Petchdee, Soontaree; Yalong, Mona; Kaewnet, Methawee; Ithisariyanont, Burasarin; Padawong, Tanawat (Frontiers in Veterinary Science, 2022)
Background Degenerative mitral valve disease is a common heart problem in dogs. The aims are to evaluate the relationships between right and left ventricular function, and blood lactate concentrations, assess prognostic contribution, and investigate whether serum peptidomics profile could reveal markers or determine the stage in dogs with valve degeneration. Materials and Methods Ninety-three dogs were evaluated in this study. Thirty-nine dogs' serum was collected and analyzed using matrix-assisted laser desorption/ionization-time of flight mass spectrometry. The Kaplan–Meier curve was used to predict the outcomes of mitral valve disease. Follow-up was obtained by a questionnaire or telephone to determine a survival time. Results The BUN/creatinine ratio, vertebral heart score, and left atrium/aorta ratio were the independent predictors of cardiac mortality. Right ventricular systolic dysfunction was found in 50% of dogs with mitral valve disease. Dogs with right ventricular dysfunction had a significantly higher incidence of lower fractional shortening and larger right ventricular dimensions. The occurrence of right-sided dysfunction is proportionate to age and the degree of left ventricular dysfunction. High blood lactate concentrations were investigated in dogs with mitral valve disease stage C compared with stage B. The peptides such as mitogen-activated protein kinase, kallikrein, and tenascin-C appeared in the heart disease progression group. Conclusion Right-hearted function assessment, blood lactate levels, and peptidomics analysis may help early detection and prognosis of this disease in dogs. Peptidomics profiles from this study demonstrate the possibility for prognosis indicators of heart valve degeneration.